Evaluation of Cardiovascular System Reactions when Different Muscle Groups are Activated - Inga Muntianaitė; Vytautas Poškaitis; Alfonsas Vainoras; Jonas Poderys; Sandra Bardauskienė (Lithuanian Sports University, 2018)
Research background and hypothesis. In our study, the dynamics of working muscle oxygen saturation of participants in the ﬁ nal stages of provocative bicycle ergometer test was different. According to this, we hypothesized, that different central and peripheral reaction of cardiovascular system would dominate during local and regional exercises, too. Research aim was to evaluate central and peripheral reaction of cardiovascular system when different muscle groups are activated. Research methods. Twenty seven healthy men (age 32 ± 1.8 years, body mass index 25.3 ± 0.6 kg / m 2 ) participated in the study. All participants performed provocative bicycle ergometer test, electrocardiogram and oxygen saturation were registered. The participants performed three exercises activating different muscle groups: calf, forearm and back extension. Research results. Variation of heart rate and oxygen saturation values highlighted the difference between arm and leg training exercises. However, the load for arms and legs was individualised, both Groups A and B were different according to the dynamics of heart rate and oxygen saturation indices. Heart rate reaction to the physical load for the back muscles was unusual - heart rate decreased during the ﬁ rst seconds of the back load. Oxygen saturation was lower in resting back muscles compared to those of resting arm and leg muscles (p < 0.05). Discussion and conclusions. The analysis of heart rate and oxygen saturation values has revealed that each functional muscle group of the human organism contains not only general but also individual activating features both integrating regulatory systems and forming a certain activation of metabolism in working muscles. Keywords: heart rate, oxygen saturation, variation of indices.